Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 195578 by sonukgindia last updated on 05/Aug/23

Answered by Frix last updated on 05/Aug/23

sin α +cos α =((√3)/3)  t=tan α  ((t+1)/( (√(t^2 +1))))=((√3)/3)  t=−((3−(√5))/2) ⇒  t^2 =((7−3(√5))/2)∧(1/t^2 )=((7+3(√5))/2)∧t^2 +(1/t^2 )=7

$$\mathrm{sin}\:\alpha\:+\mathrm{cos}\:\alpha\:=\frac{\sqrt{\mathrm{3}}}{\mathrm{3}} \\ $$$${t}=\mathrm{tan}\:\alpha \\ $$$$\frac{{t}+\mathrm{1}}{\:\sqrt{{t}^{\mathrm{2}} +\mathrm{1}}}=\frac{\sqrt{\mathrm{3}}}{\mathrm{3}} \\ $$$${t}=−\frac{\mathrm{3}−\sqrt{\mathrm{5}}}{\mathrm{2}}\:\Rightarrow \\ $$$${t}^{\mathrm{2}} =\frac{\mathrm{7}−\mathrm{3}\sqrt{\mathrm{5}}}{\mathrm{2}}\wedge\frac{\mathrm{1}}{{t}^{\mathrm{2}} }=\frac{\mathrm{7}+\mathrm{3}\sqrt{\mathrm{5}}}{\mathrm{2}}\wedge{t}^{\mathrm{2}} +\frac{\mathrm{1}}{{t}^{\mathrm{2}} }=\mathrm{7} \\ $$

Answered by mr W last updated on 05/Aug/23

sin x+cos x=(1/( (√3)))  1+2 sin x cos x=((1/( (√3))))^2 =(1/3)  ⇒sin x cos x=−(1/3)  tan^2  x+cot^2  x  =(tan x+(1/(tan x)))^2 −2  =((1/(sin x cos x)))^2 −2  =((1/(−(1/3))))^2 −2  =7

$$\mathrm{sin}\:{x}+\mathrm{cos}\:{x}=\frac{\mathrm{1}}{\:\sqrt{\mathrm{3}}} \\ $$$$\mathrm{1}+\mathrm{2}\:\mathrm{sin}\:{x}\:\mathrm{cos}\:{x}=\left(\frac{\mathrm{1}}{\:\sqrt{\mathrm{3}}}\right)^{\mathrm{2}} =\frac{\mathrm{1}}{\mathrm{3}} \\ $$$$\Rightarrow\mathrm{sin}\:{x}\:\mathrm{cos}\:{x}=−\frac{\mathrm{1}}{\mathrm{3}} \\ $$$$\mathrm{tan}^{\mathrm{2}} \:{x}+\mathrm{cot}^{\mathrm{2}} \:{x} \\ $$$$=\left(\mathrm{tan}\:{x}+\frac{\mathrm{1}}{\mathrm{tan}\:{x}}\right)^{\mathrm{2}} −\mathrm{2} \\ $$$$=\left(\frac{\mathrm{1}}{\mathrm{sin}\:{x}\:\mathrm{cos}\:{x}}\right)^{\mathrm{2}} −\mathrm{2} \\ $$$$=\left(\frac{\mathrm{1}}{−\frac{\mathrm{1}}{\mathrm{3}}}\right)^{\mathrm{2}} −\mathrm{2} \\ $$$$=\mathrm{7} \\ $$

Commented by Frix last updated on 05/Aug/23

tan x +(1/(tan x))=(1/(sin x cos x))  (1/((sin x cos x)^2 ))−2=(1/((−(1/3))^2 ))−2=9−2=7

$$\mathrm{tan}\:{x}\:+\frac{\mathrm{1}}{\mathrm{tan}\:{x}}=\frac{\mathrm{1}}{\mathrm{sin}\:{x}\:\mathrm{cos}\:{x}} \\ $$$$\frac{\mathrm{1}}{\left(\mathrm{sin}\:{x}\:\mathrm{cos}\:{x}\right)^{\mathrm{2}} }−\mathrm{2}=\frac{\mathrm{1}}{\left(−\frac{\mathrm{1}}{\mathrm{3}}\right)^{\mathrm{2}} }−\mathrm{2}=\mathrm{9}−\mathrm{2}=\mathrm{7} \\ $$

Commented by mr W last updated on 05/Aug/23

yes, thanks!

$${yes},\:{thanks}! \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com